Proses Kebertahanan Kampung Petempen Dalam Perkembangan Kota - Aprianto, Rizal (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Gajahmada become one area with great potential value in the property. Kampong Petempen located in the surrounding area are also not spared Gajahmada affected the development of property in the area. Now some homes in Kampong Petempen has been sold and have been change the high rise buildings. However, there are still some Petempen residents which still survive. The purpose of this research is to see how the adaptation done Petempen residents in order to maintain their homes of calls for the development of trade and services around it. This research was conducted with used a qualitative approach through descriptive analysis qualitative technique. Result the research can be concluded that, Kampong Petempen will gradually disappeared, The resilience process by residents just survived by means of waiting for a price deal and seeks exchange around, meanwhile the percentage of people who do not want to move by reason of comfortable live in Petempen are incredibly small. This virtue of, First, most areas of Kampong Petempen were in owned by landlords, bargaining position between residents who still stay with the developers is very low. Second, happened symbiotic mutualism between residents who status his house not certified and is the home heirs with the developers. Third, the Petempen residents who survives adapt by means of emerged as the created new economic system by opening businesses, as food stalls and boarding house.